Development and validation of novel keloid-derived immortalized fibroblast cell lines - Sadiq, Alia; Khumalo, Nonhlanhla P.; Bayat, Ardeshir (Frontiers in Immunology, 2024)
Keloids are a common connective tissue disorder with an ill-understood etiopathogenesis and no effective treatment. This is exacerbated because of the absence of an animal model. Patient-derived primary keloid cells are insufficient as they age through passaging and have a limited supply. Therefore, there is an unmet need for development of a cellular model that can consistently and faithfully represent keloid’s pathognomic features. In view of this, we developed keloid-derived immortalized fibroblast (KDIF) cell lines from primary keloid fibroblasts (PKF) by transfecting the human telomerase reverse transcriptase (hTERT) gene. The TERT gene encodes the catalytic subunit of the telomerase enzyme, which is responsible for maintaining the cellular replicative potential (cellular immortalization). Primary fibroblasts from keloid-specific lesional (peripheral, middle, and top) as well as extralesional sites were isolated and evaluated for cell line development and comparative cellular characteristics by employing qRT-PCR and immunofluorescence staining. Moreover, the immortalized behavior of KDIF cell lines was evaluated by comparing with cutaneous fibrosarcoma and dermatofibrosarcoma protuberans cell lines. Stable KDIF cell lines with elevated expression of hTERT exhibited the cellular characteristics of site-specific keloid fibroblasts. Histochemical staining for β-galactosidase revealed a significantly lower number of β-gal–positive cells in all three KDIF cell lines compared with that in PKFs. The cell growth curve pattern was studied over 10 passages for all three KDIF cell lines and was compared with the control groups. The results showed that all three KDIF cell lines grew significantly faster and obtained a fast growing characteristic as compared to primary keloid and normal fibroblasts. Phenotypic behavior in growth potential is an indication of hTERT-mediated immortalized transformation. Cell migration analysis revealed that the top and middle KDIF cell lines exhibited similar migration trend as site-specific PKFs. Notably, peripheral KDIF cell line showed significantly enhanced cell migration in comparison to the primary peripheral fibroblasts. All KDIF cell lines expressed Collagen I protein as a keloid-associated fibrotic marker. Functional testing with triamcinolone inhibited cell migration in KDIF. ATCC short tandem repeat profiling validated the KDIF as keloid representative cell line. In summary, we provide the first novel KDIF cell lines. These cell lines overcome the limitations related to primary cell passaging and tissue supply due to immortalized features and present an accessible and consistent experimental model for keloid research.